Peran publik relation dalam mempromosikan produk keuangan syariah - NOPANDIRGA, BAYUDA ZAKY (Maliki Interdisciplinary Journal, 2024)
The role of public relations (PR) in promoting sharia financial products is increasingly strategic in the context of contemporary financial markets. This research aims to analyze in depth the contribution of PR in increasing awareness, understanding and adoption of sharia financial products among the public. Through literature reviews and case studies , this research identifies a number of PR strategies that are effective in this context.The research results show that PR has a multidimensional role in promoting sharia financial products. First, PR plays a crucial role in building a positive reputation for Islamic financial institutions as institutions that are trustworthy, transparent and uphold Islamic values. Second, PR facilitates constructive two-way dialogue between Islamic financial institutions and the community. Third, PR plays a strategic role in managing the reputation of Islamic financial institutions.An effective PR strategy includes integrated communication campaigns, developing relevant and interesting content, using religious figures and influencers as endorsers, organizing outreach and educational events, and active social media management. "By implementing the right PR strategy, Islamic financial institutions can increase public trust, expand their customer base, and contribute to the sustainable development of the Islamic financial industry.